2019
DOI: 10.1371/journal.pone.0214777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different forage-to-concentrate ratios on ruminal bacterial structure and real-time methane production in sheep

Abstract: Emission from ruminants has become one of the largest sources of anthropogenic methane emission in China. The structure of the rumen flora has a significant effect on methane production. To establish a more accurate prediction model for methane production, the rumen flora should be one of the most important parameters. The objective of the present study was to investigate the relationship among changes in rumen flora, nutrient levels, and methane production in sheep fed with the diets of different forage-to-co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 65 publications
7
21
0
Order By: Relevance
“…Our study revealed higher bacterial species richness both in high-roughage diets and in the lower level of CO as revealed by rarefaction curves. The four phyla, including Bacteroidetes, Firmicutes, Proteobacteria, and Spirochaetes, were detected as major phyla in our study, which is in agreement with earlier reports (13,60). However, change in roughage-to-concentrate ratio favored two phyla Fibrobacteres and Lentisphaerae in the R70:C30 diet and one phylum Synergistetes in R50:C50 diet.…”
Section: Rumen Bacterial Diversitysupporting
confidence: 93%
“…Our study revealed higher bacterial species richness both in high-roughage diets and in the lower level of CO as revealed by rarefaction curves. The four phyla, including Bacteroidetes, Firmicutes, Proteobacteria, and Spirochaetes, were detected as major phyla in our study, which is in agreement with earlier reports (13,60). However, change in roughage-to-concentrate ratio favored two phyla Fibrobacteres and Lentisphaerae in the R70:C30 diet and one phylum Synergistetes in R50:C50 diet.…”
Section: Rumen Bacterial Diversitysupporting
confidence: 93%
“…Similar to the results of this research, concentrate and bypass fat supplementation increased protozoan population in ewes [74]. Conversely, reported by Li et al [45], showed number of total bacteria, methanogens and protozoa were decrease with the in increasing of concentrate ratio in the diet. This nding also might be differing among study because of the variation mixture in the commercialize concentrate provided to the animals.…”
Section: Effect Of Different Diets On In Vitrorumen Microbial Populationsupporting
confidence: 90%
“…The increase in these two cellulolytic bacteria in treatment groups may be due to the impact of the of ingredient contains in concentrate such as corn grain, soybean meal and rice brain, which are known to have enhancer effect on cellulolytic bacteria and eventually improve ber digestibility. With a rise in dietary starch content, the number of cellulolytic bacteria also increased signi cantly in this experiment, suggesting a shift in the carbohydrate fermentation substrate from a non-structural to structural carbohydrate [45]. The lower population of protozoa in this study, with a signi cant increase in Ruminococcus albus is described by the decline of protozoa in the rumen often results in greater proliferation of bacteria and greater passage of bacterial nitrogen N out of the rumen [68].…”
Section: Effect Of Different Diets On In Vitrorumen Microbial Populationsupporting
confidence: 47%
See 1 more Smart Citation
“…Increases in this genus have been identified previously when providing perennial ryegrass to an in vitro model of rumen fermentation (Elliott et al, 2018) and Pseudobutyrivibrio has also been identified as a native rumen bacterium that holds potential as a rumen probiotic, due to its ability to modulate in vitro fermentation to improve energy yields (Fraga et al, 2014). As Pseudobutyrivibrio has been shown to increase linearly with increasing NDF and ADF in the diet (Li et al, 2019), it is possible that the substrate provided to the model had higher proportions of these than the diet consumed by the animal. In future experiments, it would be of interest to measure enzyme activity as an indicator of changes in bacterial activity.…”
Section: Discussionmentioning
confidence: 92%